MENGUNGKAP SISI KECERDASAN DALAM PROSES PEMAHAMAN AKUNTANSI - Dewa Ayu Julia Oka; Cokorda Gde Bayu Putra (UNHI Press, 2021)
Emotional Quotient (EQ) determines how well a person uses her skills. Spiritual Quotient (SQ) is the foundation necessary for the functioning of Intellectual and Emotional quotient effectively. The informants in this study were 3 undergraduate students of Accounting Department, Faculty of Business and Tourism Economics, University of Hindu Indonesia. In this study, researchers used a qualitative approach. The research approach used was the Phenomenology of Edmund Hussel. The main objective of this research is to analyze and analyze the phenemoenology of accounting understanding from the point of view of emotional and spiritual intelligence. From the results of the research, these three informants have a weak understanding of accounting from the point of view of intelligence. This can be seen from the